A proteome map of a quadruple photoreceptor mutant sustains its severe photosynthetic deficient phenotype - Fox, Ana Romina (2015)
Light is the environmental factor that most affects plant growth and development through its impact on photomorphogenesis and photosynthesis. A quadruple photoreceptor mutant lacking four of the most important photoreceptors in plants, phytochromes A and B (phyA, phyB) and cryptochromes 1 and 2 (cry1, cry2), is severely affected in terms of growth and development. Previous studies have suggested that in addition to a photomorphogenic disorder, the phyA phyB cry1 cry2 quadruple mutant might have severe alterations in photosynthetic ability. Here, we investigated the photosynthetic processes altered in the quadruple mutant and performed a proteomic profiling approach to identify some of the proteins involved. The phyA phyB cry1 cry2 quadruple mutant showed reduced leaf area and total chlorophyll content. Photosynthetic rates at high irradiances were reduced approximately 65% compared to the wild type (WT). Light-saturated photosynthesis and the response of net CO2 exchange to low and high internal CO2 concentrations suggest that the levels or activity of the components of the Calvin cycle and electron transport might be reduced in the quadruple mutant. Most of the under-expressed proteins in the phyA phyB cry1 cry2 quadruple mutant consistently showed a chloroplastic localization, whereas components of the Calvin cycle and light reaction centers were overrepresented. Additionally, Rubisco expression was reduced threefold in the phyA phyB cry1 cry2 quadruple mutant.Together, these results highlight the importance of the phytochrome and cryptochrome families in proper autotrophy establishment in plants. They also suggest that an overall limitation in the chlorophyll levels, expression of Rubisco, and enzymes of the Calvin Cycle and electron transport that affect ribulose-1,5-biphosphate (RuBP) regeneration reduced photosynthetic capacity in the phyA phyB cry1 cry2 quadruple mutant.